Pengembangan Pengelolaan Pembelajaran Tematik Berbasis Permainan Injak Kartu Angka Pada Kelas 1 SD Negeri 2 Pulongrambe Kecamatan Tawangharjo Kabupaten Grobogan - Yuliyanti, Eni, Dr. Sabar Narimo, MM,M.Pd (2016)
The purpose of this study is to describe: (1) Management of thematic learning the teacher in class 1 at SDN 2 Pulongrambe: (2) Development of thematic learning using games stomp scorecards in class 1 at SDN 2 Pulongrambe; (3) Test the effectiveness of the management of thematic learning with games stomp scorecards developed at SDN 2 Pulongrambe. This research included in Research and Development. "Research and Development (Research and Development) is a process or steps to develop a new product or improve existing products, which can be accounted for." More research and development is a method of connecting or breaker gap anatar basic research with applied research , Research and development will result in a product that has the characteristics of a blend of a number of concepts, principles, assumptions, hypothesis, procedure with regard to something that has been discovered or generated from basic research. The results of the study are (1) Planning begins with the preparation of lesson plans, teacher planning materials, teaching methods, instructional media, learning resources and assessment techniques used. Equipped learning activity that contains the introduction, core activities, and cover with the time allocation in accordance with the competencies, learning objectives and allocation of available time. (2) The implementation of learning is good, including the ability of planning open class, capable of presenting the material, capable of using methods / media, capable of using props, capable of using communicative language, able to motivate the students, is able to organize activities, able to interact with students in a communicative, able to infer learning, able to provide feedback, is able to give an assessment, and is able to use the time. (3) The evaluation of learning has been in accordance preparation of learning (syllabus, RPP) with steps evaluation of learning that evaluation planning, evaluation, evaluation data processing, and reporting the results of the evaluation.